Stock Return and Risk Premium: Evidence from Turkey - TURSOY, Turgut; BERK, Niyazi (Journal of Advanced Studies in Finance; Vol 11 No 1 (2020): JASF Volume XI Issue 1(21) Summer 2020, 2020)
The finance theory suggests that there might be a relationship between the stock return and the risk premium. Theoretically, stock return defined as the change of the market price, and it is related to the scope of the financial system, which is consisting of the financial institution and financial markets. The way, possibly will be, to contribute the existing literature is to propose a new measurement and this study try to do so. The aim of this study and its motivation is that investigates a new measure of stock return and attempt to establish a new relationship between return and risk premium. To realise this aim, this study uses geometric mean to calculate return and standard deviation, and after all, apply panel data analysis to investigate the return and standard deviation relationship. In this study, seven commercial banks’ data analysed to the relationship between return and standard deviation with panel data analyses between 1991 and 2010. Also, the geometric mean and value relative concept used to estimate return and the monthly stock prices to yearly basis.